The TGT Learning Model Assisted by Physics Education Technology Media to Improve Critical Thinking in Mathematics on Fraction Topics - Pande Kadek Herry Adi Prastya; I Wayan Wiarta; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2025)
Mathematics learning, especially in fraction material, still faces obstacles in improving students' critical thinking skills. This study aims to analyze the effect of the Teams Games Tournament (TGT) model assisted by Physics Education Technology (PhET) in improving students' critical thinking in mathematics. This type of research is an experimental study using a quasi-experimental design. The population of this study was all third grade students in 1 group of 209 students. The research sample was divided into control and experimental classes. The data collection methods and instruments used were 25 multiple-choice tests. The data analysis technique used inferential statistical tests to measure differences in learning outcomes between the two groups. The results showed that students who learned with the TGT model assisted by PhET obtained a significant increase in critical thinking. The conclusion of this study is that the integration of cooperative learning with interactive technology can improve students' understanding of concepts and critical thinking skills in mathematics. The implications of this study are that it can provide motivation to teachers to make learning more active, innovative, and enjoyable so that students' critical thinking skills in mathematics can be achieved as expected.